Perancangan Sistem Penjualan Berbasis Website Di PT Nearby Digital Indonesia - Alif Daud Fadhulrahman; Muhammad Fikri Arzyah; Natael; Iwan Giri Waluyo (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Technological developments in the digital era now very quickly open up opportunities for business people to increase their income and expand their trading reach. This development accelerated so rapidly after the emergence of the internet. The internet provides a new method for businesses to trade their wares, which can be called a sales information system (e-commerce). One form of information technology that is popular and easy to reach for many people is mobile applications and websites. The data collection method used in this study uses the observation method where data collection is carried out to observe and review carefully and directly at the research location to find out the conditions that occur at PT Nearby Digital Indonesia and also uses the Library Study method where we collect data through references - references from various sources of articles or journals in this study. After evaluating the system in the research, the researcher proposes a new system, namely designing a sales information system that can make it easier for staff to be able to manage transaction data and transaction reports with a better system. Data Processing Efficiency: The information system designed allows PT Nearby Indonesia to process transaction data efficiently. The process of recording transaction data is done automatically, minimizing human error and saving time. The use of this system also allows merging and calculating transaction data easily, thus speeding up the processing process.